Hermeneutika Versus Maqashid (Tafsir Maqashidi) Sebagai Gerakan Membumikan Tafsir Al-Qur’an - Wely Dozan (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2021)
The study of the Qur'an has produced a number of theories and therapeutic approaches in the study of the al-Qur'an text. So far, the interpretation and study of the al-Qur'an has developed so rapidly so that the Koran is in accordance with the text and context in realizing a fair and just interpretation. This is one of the forms of the effort and movement of making al-Qur'an grounded through understanding the text and critical study in the substance. The focus of the investigation, explored the hermeneutic and maqashid approaches (Tafsir Maqashidi) then examined various aspects of the methodology, methods, application of the interpretation model, especially in relation to gender in order to see the work of the two theories in terms of interpretation. The conclusion is to ground the interpretation of the Koran, not around a textual understanding. However, the emergence of various understandings in the context of seeing the reality of society (asbabun nuzul al-Qur'an) so that interpretation is able to place a middle position (Wasthiyyah Islam). Hermeneutics and maqashid (Tafsir Maqashidi) are offered as an effort to ground the interpretation of contextual and critical nuances, taking into account the social justice of society so that it has implications according to the essence and purpose of the Qur'an being revealed.